Peran Pengawasan Dalam Meningkatkan Kinerja Karyawan Di PT. Surya Citra Solution - Ryan Febrianto; Muhammad Irwan Padli Nasution (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine and explain the role of supervision in improving employee performance at PT. SURYA CITRA SOLUTION. In carrying out this research, researchers used descriptive qualitative research. This research uses a special method which aims to explain certain phenomena in depth and the data collection technique is carried out using observations so that researchers immediately go into the field to obtain truly reliable data. The research results show that the supervisory role has a big influence in improving employee performance. Because the leader is the most dominant person and has authority and power in all efforts to create employee work discipline